Puerperal development of ewes following dystocia: a retrospective analysis of two approaches to caesarean section. (25th May 2013) - Ennen, S.; Scholz, M.; Voigt, K.; Failing, K.; Wehrend, A.
Abstract : The objective of this study was to retrospectively analyse the puerperal development of ewes referred to a veterinary teaching hospital following caesarean section in comparison with assisted parturition. Laparotomy was performed either via left flank incision (group 1, n=86) or ventral mid‐line approach (group 2, n=33). Both groups were compared with ewes following non‐surgical intervention (group 3, n=73). The overall fetal death rate was 41 per cent. There was no significant difference in fetal deaths between groups 1 and 2, but assisted delivery led to a higher number of liveborn lambs compared with caesarean section (P<0.05). Seven ewes (3.6 per cent) died or were euthanased on welfare grounds during caesarean surgery, and the overall maternal mortality rate following dystocia in the postpartum period was 10.9 per cent. While there was no significant difference between groups 1 and 2 in the percentage of ewes developing healing disorders, the complications that occurred were more severe after the left flank approach (P=0.04), and the mean hospitalisation period was significantly longer in group 1 than in group 2 (P<0.05), leading to the conclusion that ventral mid‐line laparotomy has some advantages over a left flank approach.